PENGARUH PENAMBAHAN EXTRACELLULARY POLYMERIC SUBSTANCES (EPS) DAN AGRI SIMBA SEBAGAI BIOSTIMULAN DAN BIOAUGMENTASI TERHADAP LAJU DEGRADASI LIMBAH LUMPUR MINYAK DARI IPAL PT. INDOFOOD CBP - Sheny Nurul Aini; Junaidi Junaidi; Sudarno Sudarno (Departemen Teknik Lingkungan Fakultas Teknik Universitas Diponegoro, 2013)
ABSTRACTMany environmental pollution caused by the disposal of industrial waste directly discharged into the environment, it will cause damage to the environment. Waste oil sludge has not been processed further. The high oil content of waste oil sludge will cause soil pollution in the ecosystem.In this research, waste oil sludge from WWTP PT. Indofood CBP. This study uses the technique of bioremediation in reducing the rate of degradation of waste oil sludge PT. Indofood CBP. Characteristics that can be seen is a reduction in the levels of oil concentration in the waste oil sludge.In this research, the addition of polymeric Extracellulary Substances (EPS) is useful as a nutrient in the process biostimulation, while the addition of Simba Agri useful as additional microorganisms to support bioaugmentation process. Extracellulary polymeric Substances (EPS) were added varying volume was 50 mL and 100 mL.